PRIMARY DYSMENORRHEA LEVEL BASED ON FOOD CONSUMPTION AND DIETARY HABITS IN FEMALE STUDENTS AT YWKA HIGH SCHOOL BANDUNG - Hidayah, Chintya Fatma; Sentani, Muchamad Rizki; Fitrianingsih, Asti Dewi Rahayu; Fauza, Ahdiyatul (HEARTY, 2026)
Background: Primary dysmenorrhea refers to menstrual pain that occurs before or during menstruation without any abnormalities in the reproductive organs and is most commonly experienced by adolescent girls aged 15-25 years. Globally, the prevalence reaches up to 90%, while in Indonesia it is 54.89%. Factors associated with primary dysmenorrhea include age under 30 years, early menarche, BMI under 18 kg/m², family history, and nutritional status. Objective: To examine the difference in primary dysmenorrhea level based on food consumption and dietary habit among female students at YWKA High School Bandung. Methods: This study used a quantitative design with a retrospective case-control approach. The population consisted of 96 female students from grades X and XI, with 58 students in the case group and 38 in the control group, selected using a total sampling technique. Data were collected using the SQ-FFQ and AFHC questionnaires, and analyzed using multivariate logistic regression. Results: there was an association of primary dysmenorrhea with food consumption of magnesium (OR: 2.670; 95%CI: 1.057-6.741; p-value: 0.038), family history (OR: 0.336; 95%CI: 0.133-0.853; p-value: 0.022), and dietary habit (OR: 3.432; 95%CI: 1.348-8.743; p-value: 0.01). Meanwhile, BMI (OR: 1.58; 95%CI: 0.59-4.231; p-value: 0.362) was a confounding variable. Conclusion: These findings emphasize the importance of education on balanced nutrition as part of promotive efforts to enhance reproductive health and reduce the incidence of primary dysmenorrhea among adolescent girls.